Thymus praecox subsp. polytrichus: Antimicrobial and antidiabetic activity of ethanol extracts - Grujić Slavica M.; Veličković Ivona Z.; Soković Marina D.; Petrović Slobodan S.; Petrović Nada V. (Zbornik Matice Srpske za Prirodne Nauke, 2025)
Thymus praecox is one of the most widespread species in the Euro-Siberian region. This study was conducted to determine the in vitro antimicrobial and anti-diabetic activity of its plant extracts prepared with 70% and 96% ethanol, with and without pretreatment with n-hexane, using the Soxhlet apparatus. The MICs and MBCs ranged from 0.035 to 0.150 mg/mL and from 0.075 to 0.300 mg/mL, respectively. Both 96% ethanol extracts showed the most promising antibacterial activity, especially against Bacillus cereus, Enterobacter cloacae and Salmonella Typhimurium. The pretreated 96% ethanol extract also showed remarkable antimicrobial activity against Staphylococcus aureus. Bacteria B. cereus, S. aureus and S. typhimurium were also sensitive to the pretreated 70% ethanol extract, while 70% ethanol was most effective against S. aureus and Escherichia coli. The MICs and MFCs varied from 0.017 to 0.30 mg/mL and from 0.035 to 0.70 mg/mL, respectively, with Aspergillus versicolor and Trichoderma viride being the most sensitive. The IC50 values ranged from 0.94 to 1.40 mg/mL for α-amylase and from 76.10 to 610.2 µg/mL for α-glucosidase. The 70% ethanol extract, especially with the hexane pretreatment, showed the highest enzyme inhibitory activity in the α-glucosidase assay (76.10 µg/mL), even higher than the control, acarbose/ glucobay (20.46 µg/mL). The highest α-amylase inhibitory effect was obtained for the 96% ethanol extract. The results show that the extracts of T. praecox subsp. polytrichus have significant antimicrobial and antidiabetic potential and can be used for food preservation and phytopharmacy.